Kajian Paradigma Madilog (Materialisme, Dialektika, Logika) Tan Malaka sebagai Kritik Pendidikan Islam di Madin Ath-Thoyybah Ponorogo - Andy Cahyo Wibowo (BASICA, 2025)
Traditional Islamic education faces growing challenges in adapting to the digital era and scientific advancement, reflected in low STEM literacy, limited interest in science and mathematics, and the persistence of memorization-based, dogmatic teaching that constrains critical thinking. This study investigates Tan Malaka’s Madilog (Materialism, Dialectics, and Logic) as an epistemological framework for critiquing and reforming traditional Islamic education. Using a mixed-methods approach, the research combines literature analysis of Madilog and related scholarly works with a quantitative survey of all teachers at Madrasah Diniyah Ath-Thoyyibah Ponorogo. Questionnaire data were analyzed using descriptive statistics and Kendall’s tau-b correlation in SPSS 22. The findings show that Madilog promotes rational, scientific, and systematic thinking while challenging mystical and dogmatic approaches. Its critique highlights weaknesses in traditional Islamic education, including excessive reliance on memorization, limited contextual interpretation, and insufficient cultivation of critical thinking across curriculum, teaching, and learning practices. Teachers demonstrated a high level of understanding of Madilog and expressed strong agreement with its critique of traditional Islamic education. However, no significant correlation was found between teachers’ understanding of Madilog and their responses to the critique (τ = 0.079, p = 0.775).